Efficacy of HGF Gene Transfer for Various Nervous Injuries and Disorders - Kato, Naoki; Nakanishi, Kuniaki; Nemoto, Koichi (Central Nervous System Agents in Medicinal Chemistry, 2009)
Hepatocyte growth factor (HGF) was originally identified as a molecule that could stimulate DNA synthesis in rat and human hepatocytes by autophosphorylation of the proto-oncogene c-met, which is a high-affinity receptor for HGF. Although it was at first considered that HGF could exert biological effects only on specific target cells, it has since been demonstrated that HGF mediates inflammatory responses to tissue injury and also regulates cell growth, cell motility, and morphogenesis in a wide variety of cell types, including cells within the nervous system. In the nervous system, HGF plays a role as a potent neurotrophic and angiogenetic factor. This factor promotes both the survival of neurons and the regeneration of injured nerves, and may also function as target-derived axonal chemoattractants, guiding axons to their target. These observations raised hopes that HGF protein might be useful for the clinical treatment of nervous system disorders. However, administration of HGF as a recombinant protein is still beset by a number of problems, such as a short serum half-life and poor access to the central nervous system by the systemic route because of the presence of the bloodbrain barrier. These problems can be major obstacles to the clinical use of this factor in a recombinant protein form, and has highlighted the need to develop innovative therapeutic strategies for more efficient delivery into the nervous system. Gene transfer into the nervous system has enormous therapeutic potential for a wide variety of disorders. It appears to have advantages over the administration of single or multiple bolus doses of a recombinant protein because gene transfer can achieve an optimally high, local concentration within the nervous system. In this article, we demonstrate the efficacy of HGF gene transfer and provide an overview of ideal treatment regimes for various nervous injuries and disorders.
Keywords: gene therapy